Acute effects of match-play on neuromuscular and subjective recovery and stress state in Division I collegiate female soccer players - Ishida, A.; Bazyler, C. D.; Sayers, A. L.; Mizuguchi, S.; Gentles, J. A. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to investigate acute effects of match-play on neuromuscular performance and subjective recovery and stress state and the relationship between training load (TL) and changes in neuromuscular performance in female soccer players. Twelve National Collegiate Athlete Association Division I players participated (20.7 ± 2.3 years; 64.4 ± 7.2 kg; 164.5 ± 6.0 cm) and completed countermovement jump (CMJ) at 0 kg (CMJ0) and 20 kg (CMJ20) and the Short Recovery Stress Scale (SRSS) at 3 hours pre-match (Pre), 12 hours post-match (Post12), and 38 hours post-match (Post38). Countermovement jump variables included body mass, jump height (JH), modified reactive strength index (RSI), peak force (PF), relative PF, eccentric impulse, concentric impulse (CI), peak power (PP), relative PP (RPP), eccentric average PP, and concentric average power (CAP). The SRSS consists of 4 Stress Scales (SSs) and 4 Recovery Scales (RSs). Training loads included total distance, total PlayerLoad, high-speed running, and session ratings of perceived exertion. Significant moderate to large decreases were observed from Pre to Post12 in JH, RSI, CI, PP, RPP, and CAP in CMJ0 and CMJ20 (p < 0.05, effect size [ES] = 0.63-1.35). Significant changes were observed from Pre to Post12 in all RSs (p < 0.05, ES = 0.65-0.79) and 3 SSs (p < 0.05, ES = 0.71-0.77). Significant correlations were observed between CMJ20 PP from Pre to Post12 and all TLs (p < 0.05, r = -0.58 to -0.68). CMJ0 and CMJ20 JH and PP may indicate acute neuromuscular changes after match-play. The magnitude of CMJ20 PP decrements from Pre to Post12 may be affected by soccer match-play volumes.